2019
DOI: 10.13033/ijahp.v11i2.632
|View full text |Cite
|
Sign up to set email alerts
|

Integrations and Applications of Analytic Hierarchy Process With Data Envelopment Analysis – A Literature Review

Abstract: The scope of AHP (the analytic hierarchy process) and DEA (data envelopment analysis) is widened when there is an integration of AHP and DEA to DEAHP as the same finds a lot of application areas because of its boundless flexibility and varied applicability. Furthermore, the scope, flexibility and applicability are increased manifold when DEAHP is integrated with other approaches and methods. This paper reviews the literature of the journal articles which have fond its integration with DEAHP. On the basis of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…The complex problem here is how to simply decide on the best and/or efficient criteria if there are multiple criteria important for making a decision. [ 67 ] Even though there are various MCDA methods used to generate a score, one of the quite common MCDA methods in the literature is AHP. [ 26 ] Based on a search conducted for MCDA methods through the Scopus database with the name “AHP” and “water quality” in the title, abstract and keywords, AHP is the most used MCDA method in the studies associated with water quality assessments in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…The complex problem here is how to simply decide on the best and/or efficient criteria if there are multiple criteria important for making a decision. [ 67 ] Even though there are various MCDA methods used to generate a score, one of the quite common MCDA methods in the literature is AHP. [ 26 ] Based on a search conducted for MCDA methods through the Scopus database with the name “AHP” and “water quality” in the title, abstract and keywords, AHP is the most used MCDA method in the studies associated with water quality assessments in the last decade.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially important since the complexity of financial decision problems often necessitates the use of an arsenal of analytical approaches. In light of that finding, Pradhan et al (2019) reviewed the literature on the AHP integrated with DEAHP published between 2000 and 2018, and concluded that due to its high accuracy, the integrated DEAHP approach is widely applied in the field of performance and efficiency measurement, optimization and ranking of different products or services in a variety of sectors. However, when proposing hybrid and integrated methodologies, special care should be given to keeping the resulting models as simple and user-friendly as possible.…”
Section: Literature Reviewmentioning
confidence: 99%